Changes in the product costing process driven by implementation of an integrated information system in a production company - Kamila Fałat (e-Finanse: Financial Internet Quarterly, 2019)
The article deals with product costing in a manufacturing company and change of costing methodology from normal to standard costing caused by a new integrated information system implementation. The aim of the article is to show the impact of a new integrated information system on product costing. In order to show the consequences of changing the methodology of product costing from normal to standard costing variances between standard costing and normal costing in an international production company were analyzed. For this research comparative analysis was used of unit costs before and after the new system implementation for finished goods. Ten percent of the items had a variance of more than 30% which was caused by errors in the new system settings and mistakes in the normal costs in the old system. The impact of the change of the costing methodology was shown by calculation of the difference between normal cost values and standard cost values ten months after the new integrated information system implementation. To verify the accuracy of standard costs settings, standard costs were compared to actual costs for finished goods and semi-finished goods. In the tenth period only 30% of finished goods and 42% of semi-finished goods showed a variance between standard costs and actual costs lower than 20%. It means that for the rest of the items standard cost assumptions should be checked and corrected.
Keywords: M41; O16; 330; standard costing variance; product costing; integrated information system implementation